1993
DOI: 10.1021/j100152a048
|View full text |Cite
|
Sign up to set email alerts
|

Study of the electronic structure and spectra of diphenylcarbene conformers in their ground state and lower excited states

Abstract: The triplet-triplet fluorescence of perprotonated and perdeuterated diphenylcarbene (DPC-hlo and -dlo) in n-hexane at 4.2-25 K are both composed of a sharp spectrum and a broad blue-shifted one. They are attributed to two different conformers, the sharp spectrum corresponding to DPC in a quasi-planar geometry. The excitation spectra of both emissions consist of broad bands with a large Stokes shift. A detailed CS-INDO CI investigation (configuration interaction based on an intermediate neglect differential ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 10 publications
2
18
0
Order By: Relevance
“…The To-TI transition energies of 1.96 and 1.98 eV calculated for the planar 2-NPC .conformers are lower than the corresponding energy of 2.62 eV computed for the planar (C2J DPC (9), in good agreement with the expected energy shift for more extended conjugated systems. This indicates that the CS-INDO parameters can be transferred from a medium-size molecule, like DPC, to larger compounds.…”
Section: Transition Energies Of the Conformerssupporting
confidence: 75%
See 2 more Smart Citations
“…The To-TI transition energies of 1.96 and 1.98 eV calculated for the planar 2-NPC .conformers are lower than the corresponding energy of 2.62 eV computed for the planar (C2J DPC (9), in good agreement with the expected energy shift for more extended conjugated systems. This indicates that the CS-INDO parameters can be transferred from a medium-size molecule, like DPC, to larger compounds.…”
Section: Transition Energies Of the Conformerssupporting
confidence: 75%
“…In previous reports (8,9), it was shown that two distinct fluorescence spectra are emitted from DPC in an n-hexane Shpolskii matrix over the temperature range between 4.2 and 77 K: a sharp fluorescence with an origin band at 502.8 nm and a broad blueshifted fluorescence with A, , , = 482 nm. The two fluorescence spectra were attributed to two different conformations of DPC trapped in this Shpolskii matrix.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…The lowest excited triplet state (T 1 ) was detected by triplet−triplet (T−T) fluorescence and transient absorption measurements . The zero field splitting (ZFS) parameter of D in the T 1 state of DPM has been estimated on the basis of the results of the external magnetic field effects on the T−T fluorescence decay . However, there are no reports on the EPR spectrum of the T 1 state of carbenes.…”
mentioning
confidence: 99%
“…It was also applied to the determination of accurate potential energy surfaces (for a recent example, see Ref. [70]), spin-orbit couplings in the ab initio scheme [71] or zero-field splitting parameters in a semi-empirical framework [72]. It was furthermore recently extended to semiempirical electronic Hamiltonians (PPP or CS/ INDO), using zeroth-order spaces designed to deal with the optical spectra of large conjugated systems or related ions [73][74][75][76][77][78].…”
Section: Coupling Variation and Perturbation Treatmentsmentioning
confidence: 99%